Repeated administration of a synthetic cannabinoid receptor agonist differentially affects cortical and accumbal neuronal morphology in adolescent and adult rats - Carvalho, A. F. (2016)
Recent studies demonstrate a differential trajectory for cannabinoid receptor expression in cortical and sub-cortical brain areas across postnatal development. In the present study, we sought to investigate whether chronic systemic exposure to a synthetic cannabinoid receptor agonist causes morphological changes in the structure of dendrites and dendritic spines in adolescent and adult pyramidal neurons in the medial prefrontal cortex (mPFC) and medium spiny neurons (MSN) in the nucleus accumbens (Acb). Following systemic administration of WIN 55,212-2 in adolescent (PN 37-40) and adult (P55-60) male rats, the neuronal architecture of pyramidal neurons and MSN was assessed using Golgi-Cox staining. While no structural changes were observed in WIN 55,212-2-treated adolescent subjects compared to control, exposure to WIN 55,212-2 significantly increased dendritic length, spine density and the number of dendritic branches in pyramidal neurons in the mPFC of adult subjects when compared to control and adolescent subjects. In the Acb, WIN 55,212-2 exposure significantly decreased dendritic length and number of branches in adult rat subjects while no changes were observed in the adolescent groups. In contrast, spine density was significantly decreased in both the adult and adolescent groups in the Acb. To determine whether regional developmental morphological changes translated into behavioral differences, WIN 55,212-2-induced aversion was evaluated in both groups using a conditioned place preference paradigm. In adult rats, WIN 55,212-2 administration readily induced conditioned place aversion as previously described. In contrast, adolescent rats did not exhibit aversion following WIN 55,212-2 exposure in the behavioral paradigm. The present results show that synthetic cannabinoid administration differentially impacts cortical and sub-cortical neuronal morphology in adult compared to adolescent subjects. Such differences may underlie the disparate development effects of cannabinoids on behavior.